Do we over‐diagnose ADHD in North America? A critical review and clinical recommendations. Issue 12 (23rd March 2022) - Gascon, Abigaëlle; Gamache, Dominick; St‐Laurent, Diane; Stipanicic, Annie
Abstract: There has been a marked increase in the prevalence of attention‐deficit/hyperactivity disorder (ADHD) in the last 25 years in North America. Some see this trend as positive and believe that it reflects a better identification of ADHD and even think that the disorder is still under‐diagnosed. Others, however, contend that ADHD is over‐diagnosed. To help mental health clinicians to maintain an informed and nuanced perspective on this debate, this critical review aims to (1) summarize empirical results on factors that might contribute to increase the number of ADHD diagnoses and (2) propose clinical recommendations coherent with these findings to improve clinical practices for ADHD assessment and treatment. We conclude that artifactual factors such as current formulation of diagnostic criteria, clinical practices, and inordinate focus on performance, which is rampant in North America, likely contribute to inflated prevalence rates.